2007
DOI: 10.1159/000101540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Thickness of the Cartilage Disk on the Hearing Results after Perichondrium/Cartilage Island Flap Tympanoplasty

Abstract: Objective/Hypothesis: The aim of this study was to analyze the effect of the thickness of the cartilage disk on the hearing results after perichondrium/cartilage island flap tympanoplasty. Our hypothesis was that thinning the rigid thick cartilage disk to half of its thickness could increase the compliance and give better acoustic gain and hearing results to patients with a reconstructed tympanic membrane. Study Design: A prospective before/after clinical trial was conducted between January 2003 and March 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Although in the island technique both the trimmed and nontrimmed cartilage had a better graft integration than in TF grafting, in the palisade technique only the nontrimmed cartilage had a better outcome. In agreement with our result, Atef et al 57 showed that there was no statistically significant difference in graft integration rate and hearing improvement between those treated with full-thickness and those treated with halfthickness island cartilage graft.…”
Section: Discussionsupporting
confidence: 93%
“…Although in the island technique both the trimmed and nontrimmed cartilage had a better graft integration than in TF grafting, in the palisade technique only the nontrimmed cartilage had a better outcome. In agreement with our result, Atef et al 57 showed that there was no statistically significant difference in graft integration rate and hearing improvement between those treated with full-thickness and those treated with halfthickness island cartilage graft.…”
Section: Discussionsupporting
confidence: 93%
“…Atef et al 16 analysed the effect of cartilage disc thickness on hearing results after perichondrium-cartilage island flap tympanoplasty, and concluded that slicing the cartilage to half its normal thickness added to the technical difficulties of the procedure without making a significant difference to the hearing gain. In the current study, the use of a ring graft solved this problem, by removing most of the central cartilaginous disc while keeping a narrow (2-3 mm) peripheral rim with its normal harvest thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the hypothesis that a thick, rigid cartilage disc can be associated with considerable conductive hearing loss due to reduced compliance, it could be postulated that modifying the cartilage may lead to better anatomical and audiological outcomes. A number of cartilage techniques and modifications have been described: the cartilage palisade tympanoplasty and Heermann techniques, 33 35 composite autograft shield, 27 , 36 , 37 perichondrium island flap, 24 , 25 , 38 cartilage butterfly inlay graft, 39 , 40 ‘crown cork’ technique, 41 cartilage mosaic tympanoplasty, 42 cartilage wheel, 43 cartilage slicing, 16 , 44 and cartilage reinforcement 45 . Either tragal or conchal cartilage can be used – the choice depends on the surgeon's preference 46 , 47…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A variety of techniques have been described and are currently used, including overlay, underlay, sandwich, pegging, rosette and plugging. 3,9,18 In addition, a wide variety of grafting materials have been used, in various autografts, homografts and allografts [1][2][3][4][5] At the present time, autografts of temporalis fascia, veins, areolar tissue, periosteum and perichondrium, and involving either the overlay or underlay technique, appear to be most widely used. 2,15,17 Each graft has its own, well known advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%